556. Factors Associated with Integrase Strand Transfer Inhibitor Use Between 2008 and 2015. (26th November 2018) - O'Halloran, Jane; Sahrmann, John; Olsen, Margaret A; Powderly, William
Abstract: Background: Used in conjunction with other antiretroviral drugs, integrase strand transfer inhibitors (INSTIs) are highly effective and well tolerated. First licenced in 2007, guidelines have recommended their use as an option for initial treatment of HIV since 2009. Here we examine factors associated with INSTI use. Methods: Data on people living with HIV (PLWH) who were newly initiated on antiretroviral therapy (ART) was extracted from the Truven Health MarketScan ® database for commercially insured and Medicaid covered adults between January 1, 2008 and December 30, 2015. New users were identified as those without an ART claim in the 6 months preceding study inclusion. Multivariable logistic regression was preformed to determine factors associated with INSTI use. Results: Between 2008 and 2015, 25, 928 new initiators of ART were identified. Of those 6, 000 (23%) were initiated on INSTI-based regimens (raltegravir 47%, elvitegravir 40%, dolutegravir 13%). Fifty-three percent of initiated regimens containing non-nucleoside reverse transcriptase inhibitors and 28% included protease inhibitors. Mean age was 40.4 years (10.9); 15, 382 (76%) were male. As expected, the proportion of PLWH initiated on INSTI-based regimes increased from 117 (5%) in 2008 to 53% in 2015 ( n = 1, 082). Those on INSTI were more likely male (OR 1.21 [95% CI 1.11, 1.31) and not on Medicaid (1.41, [1.29, 1.54]). Although PLWH with a history of congestive cardiac failure (1.42 [1.12, 1.8]), previous stroke (1.87 [1.03, 3.38]) or renal failure (1.48 [1.12, 1.98]) were more likely to receive INSTIs, those with a history of ischemic heart disease or risk factors for cardiovascular disease including, hypertension, dyslipidemia, obesity or diabetes were not more likely to initiate INSTI-based regimens after controlling for age and year (all P > 0.05). INSTI prescribing did not differ between infectious diseases (ID) and non-ID providers. Conclusion: Despite their good safety profile and recommendation for first-line treatment, a significant proportion of PLWH were initiated on non-INSTI-based regimens, even in the setting of underlying comorbidities. Disclosures: M. A. Olsen, Pfizer: Consultant and Grant Investigator, Consulting fee and Grant recipient. sanofi pasteur: Grant Investigator, Grant recipient. W. Powderly, Merck: Grant Investigator and Scientific Advisor, Grant recipient. Gilead Sciences: Scientific Advisor, Consulting fee.